A Bridge to Graduation: Post-secondary Effects of an Alternative Pathway for Students Who Fail High School Exit Exams - Jane Arnold Lincove; Catherine Mata; Kalena E. Cortes (Institute of Labor Economics (IZA), 2022)
High school exit exams are meant to standardize the quality of public high schools and to ensure that students graduate with a set of basic skills and knowledge. Evidence suggests that a common perverse effect of exit exams is an increase in dropout for students who have difficulty passing tests, with a larger effect on minority students. To mitigate this, some states offer alternative, non-tested pathways to graduation for students who have failed their exit exams. This study investigates the post-secondary effects of an alternative high school graduation program. Among students who initially fail an exit exam, those who eventually graduate through an alternative project-based pathway have lower college enrollment, but similar employment outcomes to students who graduate by retaking and passing their exit exams. Compared to similar students who fail to complete high school, those students who take the alternative pathway have better post-secondary outcomes in both education and employment.
Keywords: I21; I24; J18; 330; high school exit exams; high school graduation; post-secondary education; labor market outcomes; employment; earnings